Nanoscale chemical and structural investigation of solid solution polyelemental transition metal oxide nanoparticles - Abhijit H. Phakatkar; Tolou Shokuhfar; Reza Shahbazian-Yassar (iScience, 2023)
Summary: Although it has been shown that configurational entropy can improve the structural stability in transition metal oxides (TMOs), little is known about the oxidation state of transition metals under random mixing of alloys. Such information is essential in understanding the chemical reactivity and properties of TMOs stabilized by configurational entropy. Herein, utilizing electron energy loss spectroscopy (EELS) technique in an aberration-corrected scanning transmission electron microscope (STEM), we systematically studied the oxidation state of binary (Mn, Fe)3O4, ternary (Mn, Fe, Ni)3O4, and quinary (Mn, Fe, Ni, Cu, Zn)3O4 solid solution polyelemental transition metal oxides (SSP-TMOs) nanoparticles. Our findings show that the random mixing of multiple elements in the form of solid solution phase not only promotes the entropy stabilization but also results in stable oxidation state in transition metals spanning from binary to quinary transition metal oxide nanoparticles.